Study of dissolved nutrient condition at Pulau Perhentian, Terengganu - Mohamed @ Mohd Ramli, Khairul Nizam; Godon, Edrianna; Adelan @ Adnan, Nur Aklili; Abdul Rahim, Quraisha; Liew, Cynthia; Zainal Abidin, Aizad Imran; Zainuddin, Mohamad Faiz (Universiti Putra Malaysia Press, 2019)
This study compares the distribution of dissolved nutrients (NO3− and PO43−) between two seasons (pre-monsoon and post-monsoon) in Pulau Perhentian, Terengganu. The concentration of dissolved PO43− was found to be 16 to 83 times higher during the post-monsoon period (April 2015) compared to the pre-monsoon period (October 2014). On the other hand, the concentration of dissolved NO3− was two (2) to three (3) times higher during the post-monsoon period (April 2015) compared to the pre-monsoon period (October 2014). These nutrients’ inputs were converted from P limitation condition during the pre-monsoon period to N limitation condition during the post-monsoon period at our study area. The results of this study suggest that the Northeast monsoon plays an important role in influencing the distribution of dissolved nutrients between seasons in Pulau Perhentian. It is thought that during the post-monsoon period, a considerable input of nutrients from bottom water is responsible for increasing dissolved nutrients in surface water, in particular PO43−.